Evolução do processo erosivo na margem direita do rio São Francisco e eficiência dos enrocamentos no controle da erosão - Bandeira, Arilmara Abade (2005)
The construction of big electrical power dams on the São Francisco river channel have led to changes in its hydrological system and altered its discharge and sediment s transport behaviour, and then generating some environmental impacts and potencialized others. The accelerated bank erosion is considered one of the most harmful ones leading to application of various of alternatives in order to control it and consequently the channel sedimentation. This research was developed in order to monitor bank erosion process in the right margin of the Low San Francisco River, during January 2004 until February 2005, in four different sites located from Propriá to the river estuary, studying the possible causes and also the riprap efficiency in order to control the river bank erosion. The pegs methods was used to measure erosion rate and to describe it the profiling method was used in four different sites (A, B, C and D). Water Level Indicators in three of the studied sections was installed in order to study the subterranean waters flux on the river banks. The annual rates of bank erosion was 2,06 meter to site A, 4,06 meter to site B, 4,35 meter to site C and 10,03 meter to site D. They are lower numbers then was recorded in previous years, explained by the redesign of the bank morphology promoted by the occurenc of January 2004 flood, which promotes an apparent stabilization of the erosion process. The variation of erosion among the sites was related to the localization, soil texture, the bank height climate and hydrological features, also wind speed, monthly amplitude waves near the edge and the hydraulic flux from soil to the river. The behavior of riprap constructed in order to control the erosion is efficient in the most of locals they were implanted, although they could collapse in the future because of lack of studies related to the river morphological changes near them. These data can subsidy public decisions in order to minimize the environment negative impacts caused by unsustainable natural resources uses in the San Francisco River Basin.